STUDI PENGARUH PH TERHADAP KONSENTRASI ALUMINIUM TERLARUT DARI -KAOLIN - NESBAH
Under kaolin is understood the rock mass composed essentially of a clay material that is usually white or nearly white in color, low in iron and composition of 39,5% Al203, 41,54% SiO2, and 13,90 % H20. .In this research the effect of mixing time, ratio of kaolin-aquades composition, and pH on concentration of dissolved aluminum of kaolin were studied. The concentration of dissolved aluminum in solution was determined spectrophotometrically as the aluminum-aquinolate comlex extracted in chloroform. The experimental results show that concentration of dissolved aluminum for any ratio of kaolin-aquadest composition increases with a increasing mixing time, after reaching a maximum, the concentration of dissolved aluminum decreases with a increasing mixing time. Whereas the effect of pH was to increase the concentration of dissolved aluminum in the acid state (low pH) as well as in the basic state (high pH) compared to the neutral state.